Pengaruh Ekstrakurikuler Rohis terhadap Karakter Religius Siswa di SMA Negeri 1 Bojong Gede - Hartati, Aliyah; Supriadi, Dedi; Triwoelandari, Retno (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The purpose of this study was to determine the effect of extracurricular rohis on student character at SMA Negeri 1 Bojonggede. This research was conducted from February to August 2023. The number of samples was 55 which were determined using saturated samples and Sugiyono's theory. The data were analyzed using a survey method with a quantitative approach. The results of the study obtained that Rohis extracurricular activities have a positive effect on student character at SMA Negeri 1 Bojonggede. The hypothesis was answered with Ha accepted and H0 rejected using the correlation coefficient test. Through the correlation test, a significance value of 0.001>0.05 was obtained, meaning that there is a relationship between extracurricular spiritual activities and the religious character of students at SMA Negeri 1 Bojonggede. Obtained rcount 0.433>0,2656 shows a positive relationship. In creating a generation with religious character, a joint effort is needed between educators, students and parents. It takes knowledge, awareness and appreciation of religion in the school and social spheres.